Medical Imaging 2023: Physics of Medical Imaging 2023
DOI: 10.1117/12.2655716
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical basis and experimental validation of harmonic coherence-based ultrasound imaging for breast mass diagnosis

Abstract: Coherence-based ultrasound imaging has demonstrated potential to improve breast mass diagnosis by distinguishing solid from fluid-filled masses. Harmonic imaging, which is known to reduce acoustic clutter, has the potential to offer additional improvements. However, the lack of a theoretical basis to describe these improvements precludes clinical recommendations based on physics and engineering principles. This work is the first to develop a theoretical model of coherence-based ultrasound imaging to describe b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…In fundamental and harmonic SLSC images, dark regions are visible at the boundary of the mass (and in other areas of the tissue). These dark regions, representing areas of low spatial coherence and previously identified as artifacts [32], are more prominent in the fundamental coherence images when compared to matched harmonic coherence images. These darkregion artifacts are not unique to breast images, and they typically appear in coherence images when bright, coherent regions exist laterally to a less coherent region [18].…”
Section: A Example Amplitude and Coherence Imagesmentioning
confidence: 72%
See 2 more Smart Citations
“…In fundamental and harmonic SLSC images, dark regions are visible at the boundary of the mass (and in other areas of the tissue). These dark regions, representing areas of low spatial coherence and previously identified as artifacts [32], are more prominent in the fundamental coherence images when compared to matched harmonic coherence images. These darkregion artifacts are not unique to breast images, and they typically appear in coherence images when bright, coherent regions exist laterally to a less coherent region [18].…”
Section: A Example Amplitude and Coherence Imagesmentioning
confidence: 72%
“…In addition, Wiacek et al [30] demonstrated that including R-SLSC images alongside B-mode images would have decreased the percentage of unnecessary biopsies from 43.3% to 13.3%, due to the improved diagnostic certainty of breast ultrasound images when assessed by five board-certified radiologists in a randomized reader study. Sharma et al [31] and Kokumo et al [32] combined harmonic imaging with R-SLSC imaging and SLSC imaging, respectively, to assess additional potential benefits of these combinations. Despite these advances, variations among radiologists were observed when diagnosing breast masses during the reader study noted above, highlighting the importance of reader-independent metrics to distinguish solid from fluid masses [23], [30], [33].…”
Section: Highlightsmentioning
confidence: 99%
See 1 more Smart Citation